Análise da permeabilidade de argamassas estabilizadas submetidas a tratamento superficial com aditivos cristalizantes - Jantsch, Ana Cláudia Akele (2015)
Water presence is one of the major causes of pathological manifestations in mortar coatings. Such problem endangers the material durability, and the protection ability of these coatings, thus allowing early degradation of materials and structures. On the other hand, the use of waterproofing treatment promises to solve this issue, creating a barrier to water penetration. However, few non-commercial studies are found on this matter, even rarer are the researches that focus on ready-to-use mortars. Therefore, the present study sought to analyze 36h and 72h ready-to-use mortars produced in the city of Santa Maria with and without the application of crystallizing treatment to evaluate these mortars performance. The methods consisted in evaluating the fresh and hardened characteristics of these materials. At the end of the experiments, it was concluded that the 36h mortar showed superior performance in comparison to the 72h mortar and although the application of crystallizing treatments did not waterproof the mortars, it did contributed to reduce their water absorption, abrasion resistance and improve vapor permeability.